Turnover, richness difference and nestedness of rodent assemblages along the southern Andes elevation gradient. (3rd December 2020) - Novillo, Agustina; Ojeda, Ricardo
Abstract: Beta diversity in ecological communities can reflect adaptations of species to differences in climate, environmental characteristics and site history, as well as local ecological dynamics. These dissimilarities among communities may reflect different processes as species replacement and richness difference or nestedness, which can be generated by different factors. Assemblages in mountain regions are expected to exhibit high beta diversity due to sharp environmental variation and historical events promoting isolation. Diversity patterns of small mammals along elevation gradients in the southern dry Andes exhibit high richness among high elevations and a humped shape pattern for abundances. However, it is not clear how beta diversity changes along this gradient, or the processes involved in this variation. Here we aim to evaluate small mammal beta diversity patterns along the elevation gradient. Therefore, we decomposed beta diversity into spatial turnover, richness differences and richness differences as a result of nestedness. Assemblage structure variation was assessed qualitatively and quantitatively. Also, we evaluate the local contribution of beta diversity (LCBD) and species contribution to beta diversity, to identify priority conservation sites and species. Our results show contrasting patterns among qualitative and quantitative beta diversity components. The former was mainly explained by species turnover, while the latter showed a higher contribution of richness difference than species turnover. Most components of beta diversity decreased with elevation, except for abundance turnover that showed an opposite trend. Furthermore, LCBD was higher at lower and mid‐elevation sites and exhibited a negative relationship with species richness and abundance. Abstract : How species composition varies from one site to another and which mechanisms are involved in structuring this variation is one of the roots of community ecology and biogeography studies. Decomposing small mammals beta diversity along the southern dry Andes elevation gradient showed contrasting patterns among species composition accounted for by species richness and species abundances. The former was explained mainly by spatial turnover, probably through mechanisms including environmental filtering, species sorting, and dispersal limitation. While the latter is almost equally explained by turnover and abundance difference, supporting a mixed pattern where local process as niche requirements and biotic interactions outline species abundances along the elevation gradient. High turnover was registered at the transition between the Monte desert and Altoandina ecoregion, emphasizing this region as the one with the highest contribution to beta diversity. However, this region also supports a few species that are at low abundances. This transition zone can be considered as a marginal region for species of high elevations and those typical of the lowland Monte desert. Resumen: La diversidad beta en las comunidades ecológicas puede reflejar las adaptaciones de las especies a las diferencias en el clima, las características ambientales y la historia del sitio, así como la dinámica ecológica local. Estas diferencias entre comunidades evidencian diferentes procesos como el recambio de especies y la diferencia de riqueza o anidamiento, que pueden ser generados por diferentes factores. Se espera que los ensambles en las regiones montañosas exhiban una alta diversidad beta debido a la fuerte variación ambiental y los eventos históricos que promueven aislamiento. Los patrones de diversidad de los pequeños mamíferos a lo largo de los gradientes de elevación en los Andes áridos del sur, exhiben mayor riqueza en zonas más elevadas y un patrón de forma jorobada intermedia para las abundancias. Sin embargo, no está claro cómo cambia la diversidad beta o los procesos involucrados en esta variación, a lo largo de este gradiente. Nuestro objetivo es evaluar los patrones de diversidad beta de los pequeños mamíferos a lo largo del gradiente de elevación. Por lo tanto, descompusimos la diversidad beta en recambio espacial, diferencias de riqueza y diferencias de riqueza como resultado del anidamiento. La variación de la estructura del ensambles se evaluó cualitativa y cuantitativamente. Además, evaluamos la contribución local de la diversidad beta (LCBD) y la contribución de las especies a la diversidad beta (SCBD), para identificar especies y sitios de prioritarios para conservación. Nuestros resultados muestran patrones contrastantes entre los componentes de diversidad beta cualitativos y cuantitativos. Lo primero se explica principalmente por el recambio de especies, mientras que la segunda mostró una mayor contribución de la diferencia de riqueza. La mayoría de los componentes de la diversidad beta disminuyeron con la elevación, excepto por el recambio de abundancias que mostró una tendencia opuesta. Además, la LCBD fue mayor en los sitios de elevación media y baja y mostró una relación negativa con la riqueza y abundancia de especies. Abstract in Spanish is available with online material.